Broken Legs, Clinical Overrides, and Recidivism Risk: An Analysis of Decisions to Adjust Risk Levels With the LS/CMI - Guay, Jean-Pierre (Criminal justice and behavior, 2018)
Risk assessment practices have evolved considerably over the past three decades. Structured assessments of recidivism risk allow for the proper identification of criminogenic needs, which in turn, allow decision makers to make informed recommendations regarding criminal justice interventions and measures. Although actuarial assessments are common practice, situations exist where evaluators may call into doubt the risk assessment’s conclusions, and may exercise their discretionary professional judgment to adjust the risk rating. Despite being common practice, clinical overrides have been the subject of very little empirical work. The aim of the current study is to examine the impact of clinical overrides on a large sample of individuals (N = 3,646) who were assessed using the Level of Service/Case Management Inventory (LS/CMI). Findings demonstrate that upward overrides produce different results than downward overrides. The practical and theoretical implications of these results are discussed.